Validation of the arabic version of the EuroQol-5-dimension 5-level (EQ-5D-5 L) in patients with spinal degenerative diseases - Ahmed Shawky Abdelgawaad; Mohammad El-Sharkawi; Ahmed Mahmoud Sarhan; Mohammed Abdelghafour Hassanien; Mirette Aziz (BMC, 2024)
Abstract Objective This study aims to test the reliability and validity of the translated Arabic version of EQ-5D-5 L. Methods The study was conducted on 100 patients operated upon for degenerative spine diseases coming for follow up in the outpatient clinic of a Tertiary care hospital. Test-retest reliability was assessed by completing the self-administered tool in two follow up visits, one week apart, by 50 patients. Internal consistency was evaluated by Cronbach's alpha. Intra-class correlation coefficients and kappa statistics were performed to test for the agreement between the two ratings. Criterion validity was assessed by comparing the responses of 100 patients to the EQ-5D-5 L with scores of two validated questionnaires; the Arabic version of the Oswestry disability index and the Arabic version of short-form health survey-36. The construct validity was assessed using known-groups comparison to test for hypothesized differences concerning demographic and clinical variables. Results The Arabic version of EQ-5D-5 L questionnaire had a high reliability with high observed internal consistency (Cronbach's alpha = 0.816, CI: 0.719-0.886). It showed strong temporal stability, with ICCs of the EQ-5D-5 L score, index and EQ-visual analog scale (EQ-VAS) of 0.852, 0.801, and 0.839 respectively. Agreement by kappa was moderate; above 0.4, for all domains, except for the "Usual activities" domain. EQ-5D-5 L domains, VAS and index had moderate to strong significant correlations with SF-36 and ODI subscales and total scores in the correct direction indicating a good criterion validity of the instrument. Conclusion The Arabic version of EQ-5D-5 L is reliable and valid for assessment of HRQoL of Arabic speaking patients.